Use of current S355 and S690 steels for arctic applications: - Walters, C.L.; Dragt, R.C.; Romeijn, E.; Weijde, G.D. van der (2014)
In this paper, the applicability of currently-available S355 and S690 steels to Arctic applications is estimated according to current classification rules. A database of results used for quality control for offshore structures that were not necessarily designed for Arctic operations was analyzed. The results needed to be extrapolated to lower temperatures in order to make a comparison against the test temperatures specified by the codes. The results showed that 72% of current S690 steels and 55% of current S355 steels would be applicable to Arctic conditions if they had been tested and graded for that application according to ABS, BV, or IACS rules.